Climbing the job ladder: New evidence of gender inequity - David W. Johnston; Wang-Sheng Lee (Institute for the Study of Labor (IZA), 2011)
An explanation for the gender wage gap is that women are less able or less willing to 'climb the job ladder.' However, the empirical evidence on gender differences in job mobility has been mixed. Focusing on a subsample of younger, university-educated workers from an Australian longitudinal survey, we find strong evidence that the dynamics of promotions and employer changes worsen women's labour market position.
urn:nbn:de:101:1-201110102178
Keywords: J16; J33; J71; 330; promotions; job changes; gender; wage gap; Lohndifferenzierung; Erwerbsverlauf; Arbeitsmobilität; Australien